An application of PRECIS-2 to evaluate trial design in a pilot cluster randomised controlled trial of a community-based smoking cessation intervention for women living in disadvantaged areas of Ireland - Hayes, Catherine; Darker, Catherine (My University, 2022)
“We Can Quit2” (WCQ2) was a pilot cluster randomised controlled trial with an embedded process evaluation assessing the feasibility and acceptability of ‘We Can Quit’ (WCQ), a peer-delivered community-based stop-smoking programme for women in disadvantaged communities. The control group comprised ‘enhanced usual care’ offered by the Irish Health Service Executive (HSE). The PRagmatic Explanatory Continuum Indicator Summary (PRECIS-2) is a tool to assess whether a trial design is more explanatory (working under ideal conditions) or pragmatic (working under ‘real world’ conditions). The aim of this paper was to retrospectively evaluate the WCQ2 pilot trial using PRECIS-2 to inform the decision-making process on progression to a future definitve trial (DT). Methods The WCQ2 trial protocol and HSE standard stop-smoking service were described across the nine PRECIS-2 domains: Eligibility, Recruitment, Setting, Organisation, Flexibility-Delivery, Flexibility-Adherence, Follow-up, Primary Outcome. Team members scored the domains as pragmatic or explanatory for each arm in a half-day workshop. Results Seven team members (practitioners and researchers) assessed the overall trial design as more explanatory than pragmatic. Important differences emerged between the two arms. WCQ targeted adult women from disadvantaged communities whereas HSE run a limited enhanced service for all quitters. Recruitment to trial was challenging, intense efforts were needed as the trial proceeded. WCQ was delivered in a non-clinical community setting, HSE services in a clinical setting. WCQ organisation was co-designed with community partners and comprises peer-to- peer group support delivered by trained lay community facilitators, whereas HSE one-to-one support is delivered by Smoking Cessation Officers with a clinical background. Only WCQ allowed flexibility in delivery and adherence. Follow-up was more intensive in WCQ. Greater efforts to improve participant retention will be required in a future DT. Conclusions PRECIS-2 allowed the reflection of practitioners and researchers on similarities and differences between intervention and control arms. Results will inform the decision on progression to an effectiveness DT, which will require more a pragmatic and less explanatory design. This novel use of PRECIS-2 to retrospectively evaluate a complex community-based pilot trial in advance of a full DT will also support learning for those undertaking hybrid trials of implementation and effectiveness.
PUBLISHED
Keywords: PRECIS-2; Pragmatic trial; Process evaluation; Implementation; Smoking cessation; Women; Deprivation; Pilot and feasibility study; Trial design; Inclusive Society